Study On Establishing National Standard Of Vocational Teachers’ Training In China - Yu, Qiding (Journal of Technical Education and Training, 2009)
Developing vocational education is an important strategy in current Chinese education. However, vocational teachers are in a shortage and there isn’t a sound system of training and cultivating these teachers. Especially, there hasn’t formed any effective standard of vocational teachers. These three factors are the main reasons to hinder the development and increase of its quality and level. Therefore, establishing national standard of vocational teacher training is becoming very necessary. In this paper the author explores the standard and system of vocational teacher training from two aspects, namely, grasping professional skills and professional teaching competence. National standard of vocational teacher training will become a basis for vocational teacher qualification. According to this standard, vocational teacher qualification curriculum will be built and implemented by vocational educational institutions. We will share our experiences and measures in building vocational teacher qualification system in China and explore some key issues.